Surgical Pathology Resident Rotation Restructuring at a Tertiary Care Academic Center - Chelsea R. Mehr MD; Amrom E. Obstfeld MD, PhD; Amanda C. Barrett MD; Kathleen T. Montone MD; Lauren E. Schwartz MD (Elsevier, 2017)
Changes in the field of pathology and resident education necessitate ongoing evaluation of residency training. Evolutionary change is particularly important for surgical pathology rotations, which form the core of anatomic pathology training programs. In the past, we organized this rotation based on subjective insight. When faced with the recent need to restructure the rotation, we strove for a more evidence-based process. Our approach involved 2 primary sources of data. We quantified the number of cases and blocks submitted per case type to estimate workload and surveyed residents about the time required to gross specimens in all organ systems. A multidisciplinary committee including faculty, residents, and staff evaluated the results and used the data to model how various changes to the rotation would affect resident workload, turnaround time, and other variables. Finally, we identified rotation structures that equally distributed work and created a point-based system that capped grossing time for residents of different experience. Following implementation, we retrospectively compared turnaround time and duty hour violations before and after these changes and surveyed residents about their experiences with both systems. We evaluated the accuracy of the point-based system by examining grossing times and comparing them to the assigned point values. We found overall improvement in the rotation following the implementation. As there is essentially no literature on the subject of surgical pathology rotation organization, we hope that our experience will provide a road map to improve pathology resident education at other institutions.